S. Cosentino (ed.), A Companion to Byzantine Italy - Tartaglia, Luigi (Sefer yuḥasin ספר יוחסין | Review for the History of the Jews in South Italy | Rivista per la storia degli ebrei nell’Italia meridionale, 2021)
Recensione